Proporcionalidade à luz da Teoria dos Campos Conceituais: uma sequência de ensino diferenciada para estudantes da EJA - Macedo, Eduardo Lopes de (2012)
This research aimed at investigating the potential of a teaching material which had been designed based on the previous knowledge of Adult Education students and under the perspective of the Theory of Conceptual Fields for the learning of the concept of Simple Proportion. Aiming at meeting the objective above, a quasi-experimental study was designed to be applied with two classes at a state school in the city of São Paulo. These classes constituted two groups of 20 students; the control group (CG) who received conventional classes on the subject of Simple Proportion - and the experimental group (EG) who underwent a different teaching intervention, based on the apprehension of the concepts by means of situations that were representative of the students daily practices. Participants underwent a pre-test at the beginning of the research and a post-test after the intervention had been carried out. The theoretical framework for this research encompassed the theory of Conceptual Fields, as proposed by Vergnaud (2009). We also used the correlated study by Magina, Santos, Merlini (in press). We have decided to investigate our results by means of two types of analyses: quantitative analysis, carried out by means of comparisons between groups and our research variables; and qualitative analysis, carried out by interpreting strategies employed in the solution of problems, and by interpreting the mistakes made by the students. For reliability purposes, data analyzed quantitatively were treated statistically. Analyses show that on the post test, the EG students had a meaningful improvement; matching their results on the variables of analyzed researched; improved the use of known strategies; internalized new solution strategies. Results allowed us to infer that the learning process of the concept of Simple Proportion is effective when based on adult students previous knowledge, and within the perspective of the Theory of Conceptual Fields. At the end of the study, students showed a broader understanding of the concept studied, besides showing an enhanced capacity of reflection about the use of the more effective strategies for the solution of proposed problems